Helical Propensity in an Intrinsically Disordered Protein Accelerates Ligand Binding1. Issue 6 (21st January 2014) - Iešmantavičius, Vytautas; Dogan, Jakob; Jemth, Per; Teilum, Kaare; Kjaergaard, Magnus
Abstract Many intrinsically disordered proteins fold upon binding to other macromolecules. The secondary structure present in the well‐ordered complex is often formed transiently in the unbound state. The consequence of such transient structure for the binding process is, however, not clear. The activation domain of the activator for thyroid hormone and retinoid receptors (ACTR) is intrinsically disordered and folds upon binding to the nuclear coactivator binding domain (NCBD) of the CREB binding protein. A number of mutants was designed that selectively perturbs the amount of secondary structure in unbound ACTR without interfering with the intermolecular interactions between ACTR and NCBD. Using NMR spectroscopy and fluorescence‐monitored stopped‐flow kinetic measurements we show that the secondary structure content in helix 1 of ACTR indeed influences the binding kinetics. The results thus support the notion of preformed secondary structure as an important determinant for molecular recognition in intrinsically disordered proteins.